2001
DOI: 10.1021/om001013o
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Redox Properties of a Cp*Co(dithiolene) Complex. Evidence of the Formation of a Dimeric Dicationic Species:  [Cp*Co(dddt)]22+ 

Abstract: The synthesis and the electrochemical characterization of [(η 5 -C 5 Me 5 )Codddt] (dddt 2-) 5,6-dihydro-1,4-dithiine-2,3-dithiolate) (1) are described. The chemical oxidation of 1 by AgBF 4 leads to the formation of a bimetallic complex, [(η 5 -C 5 Me 5 )Codddt] 2 2+ (2), which has been characterized by X-ray crystallography. The 1 H NMR study reveals that 2 is diamagnetic, and this has been rationalized by extended Hu ¨ckel calculations. The addition of trimethyl phosphite on 2 gives the paramagnetic adduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…oxidation have been reported [15,16], our example is the first case of the electro-oxidative dimerization of a ruthenium dithiolene complex. In oxidation process, complexes 1b and 1c showed several re-reduction waves after oxidation.…”
Section: Electrochemical Behavior Of Ruthenium Dithiolene Complexesmentioning
confidence: 79%
See 2 more Smart Citations
“…oxidation have been reported [15,16], our example is the first case of the electro-oxidative dimerization of a ruthenium dithiolene complex. In oxidation process, complexes 1b and 1c showed several re-reduction waves after oxidation.…”
Section: Electrochemical Behavior Of Ruthenium Dithiolene Complexesmentioning
confidence: 79%
“…We focused on the unsaturated character of the ruthenium-sulfur bond in the dithiolene ring, and we report on the novel cycloaddition reactions into the unsaturated bond. Furthermore, metalladithiolene complexes are sometimes promoted to undergo the dimerization reactions by an oxidation [15,16]. One example, which is reported by Fourmigué et al [16] is shown in Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voltammetric data of 2 and its P(OMe) 3 adducts and for a dithiolene cobaltocene complex. [16] With this latter complex, it has also been shown that in the presence of a strong two-electron donor ligand the stabilization occurs via the formation of an adduct. [16] Thus, in order to explain the mechanism of the oxidation of 2 in the presence of a strong Lewis base, electrochemical experiments were conducted in CH 2 Cl 2 , where an excess of P(OMe) 3 was initially added to 2.…”
Section: Electrochemical Experimentsmentioning
confidence: 99%
“…The electrochemical oxidations of the mononuclear cobalt dithiolene complex [Cp * Co(dddt)] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate) [29] and the mononuclear ruthenium dithiolene complex [(C 6 H 6 )Ru{S 2 C 2 (COOMe) 2 }] [15] undergo dimerizations. This process is a unique case, because the reduction of a dimeric dithiolene complex gives a monomer.…”
Section: Electrochemical Behavior Of Molybdenum Dithiolene Complexesmentioning
confidence: 99%